The Impact Of Using Shopee Paylater On Student Consumptive Lifestyle Consumptive Lifestyle Of College Students - Rafidah, Dita Dinar; Nurjaman, Asep Rudi (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2024)
The purpose of this research is first, to find out the use of paylater shopee among students, second, to find out the consumptive behavior of students, third, to find out the effect of using paylater shopee on student consumptive behavior. Like the Paylater in the Shopee application, you can immediately use it when selecting a payment method to use the Shopee feature with limits set by the application. Paylater Shopee is a paylater provider that can be used to pay for certain products, provided that the merchant must work with GoJek previously. The increasing level of online shopping with various payment options, especially the paylater that has been provided, has led to new lifestyle patterns and consumer behavior in online shopping habits.